A produção de sentido no consumo de fofocas: uma análise das interações no perfil Choquei do Instagram - Caro, Letícia Franco (2025)
This research investigates the public's production of meanings in relation to the Choquei profile on Instagram, one of the main profiles specialized in disseminating gossip about entertainment and digital culture. Inserted in the field of Communication and Consumption, the study aims to understand how users interpret and give new meaning to the content shared by this profile, based on the analysis of interactions in the comments on posts. To this end, the research includes a bibliographical review on consumer culture, in addition to mapping the evolution of gossip, from its traditional manifestations to its consolidation in digital profiles. The methodology adopted is based on french discourse analysis, as proposed by Orlandi (2005), allowing the investigation of the meanings produced from discursive interactions in the digital environment. Data collection focused on the most liked comments of Choquei's five most commented posts about Big Brother Brasil 2025, ensuring the representativeness of the analyzed corpus. The results show that users not only consume gossip, but also actively participate in the construction of meaning, promoting judgments, validations and criticisms that influence both the credibility of specialized profiles and the public image of influencers and celebrities.